Vinland saga. Book fourteen - Yukimura, Makoto, 1976- (Kodansha Comics, 2025)
The first wheat grown in Arnheid Village sways in the breeze, Gudrid is pregnant, and Hild has finally let go of her need for vengeance. The new world that Thorfinn dreamed of, a world without war or slavery, seems within reach. Yet history is a tide that too often sweeps away individuals with good intentions, and there are those among the Lnu who believe that continued toleration of these newcomers will end in disaster, and some among the Norsemen who still hold onto a belief in physical force as a first, not last, resort. What will sprout from this seed of uncertainty, alongside the golden grain...?